Modeling of the time trial cyclist projected frontal area incorporating anthropometric, postural and helmet characteristics - Barelle, C.; Chabroux, V.; Favier, D. (Sports Engineering, 2010)
In time trial cycling stage, aerodynamic properties of cyclists are one of the main factors that determine performances. Such aerodynamic properties are strongly dependent on the cyclist ability to get into the most suitable posture to have minimal projected frontal area facing the air. The accurate knowledge of the projected frontal area (A) is thus of interest to understand the performance better. This study aims for the first time at a model estimating accurately A as a function of anthropometric properties, postural variations of the cyclist and the helmet characteristics. From experiments carried out in a wind tunnel test-section, drag force measurements, 3D motion analysis and frontal view of the cyclists are performed. Computerized planimetry measurements of A are then matched with factors related to the cyclist posture and the helmet inclination and length. Data show that A can be fully represented by a rate of the cyclist body height, his body mass, inclination and length of his helmet. All the above-mentioned factors are thus taken into account in the present modelling and the prediction accuracy is then determined by comparisons between planimetry measurements and A values estimated using the model.